Damage patterns, stress rotations and pore fluid pressures in strike-slip fault zones - Healy, David (American Geophysical Union, 2008)
Active faults unfavorably oriented with respect to the regional maximum compressive stress have been labeled as "weak." The seismic hazards posed by these faults make understanding this apparent weakness a priority. Stress rotations in these fault zones, together with an increase in mean stress, could enable high pore fluid pressures to weaken a fault zone. Such a model requires a foundation in the physics and mechanics of damage. This paper presents a new model for stress rotations in fault zones by combining the Effective Medium Theory with anisotropic poroelasticity. This approach enables the quantitative characterization of crack damage and the prediction of progressive changes in the elastic properties of rocks across the fault zone. The processes of fault growth and wear will lead to distinct patterns of crack damage, with different effects on the elastic properties. Elevated pore fluid pressures have long been known to change the effective normal and shear stresses of anisotropic rocks, and this work incorporates these effects into a multilayer fault zone model. It is shown that high pore fluid pressures in the anisotropic rocks of the core zone can generate large stress rotations (i.e., more fault-parallel), and increases in mean stress, sufficient to weaken the fault. Stress rotations in the damage zones of unfavorably oriented faults tend to be away from the fault (i.e., more fault-normal) for likely combinations of damage patterns and pore fluid pressure.